EU Influence on the Cyprus Issue: From Association to Accession - Christou, George (Études helléniques / Hellenic Studies, 2003)
With the signing of che Accession Treary in April 2003, the European Union took a historic step to admit ten more countries by May 2004, including Cyprus. While the decision to include Cyprus was met with general euphoria, this was undermined by the fact that the accession process and the decision to enlarge had not led to a solution of the Cyprus issue. The degree to which the accession process can help trigger a solution has been a controversial issue since 1993, when the European Commission issued its Opinion (Avis) on the application of Cyprus for membership. The EU has always been optimistic, although there has been a gap between expectation and outcome in reality. lt is the purpose of this paper to assess the thinking of EU policymakers on the Cyprus issue and the impact of the enlargement process on promoting a more conciliatory climate for cooperation among the parties involved.